Inequality Is Bad for the Poor - Ravallion, Martin (Washington, DC: World Bank, 2012)
It has been argued that inequality should be of little concern in poor countries on the grounds that 1) absolute poverty in terms of consumption (or income) is the overriding issue in poor countries and 2) the only thing that really matters to reducing absolute income poverty is the rate of economic growth. The author takes 1) as given but questions 2). He argues that there are a number of ways in which the extent of inequality in a society, and how it evolves over time, influences the extent of poverty today and the prospects for rapid poverty reduction in the future.